A raypath-consistent receiver correction in PS converted wave processing through seismic interferometry: New application for tropical zones New application for tropical zones - Andrés Salamanca, Luis Montes (Universitas Scientiarum)
The estimation of static corrections is an issue still unsolved for PS converted wave processing. Due to the PS converted wave usually arriving at the surface at non-zero angles, the surface consistent approach is no longer valid, and corrections become non-stationary, i.e. the correction is not static. Seismic interferometry is used in receiver gathers transformed to the radial domain to estimate functions that contain the delay caused by the weathered layer, considering the emergence angle of the PS converted wave. Inverse filters, derived from these functions, are applied by convolution to the raw traces to supply traces corrected for weathering layer effects. Seismic interferometry was satisfactorily tested in two synthetic models and then applied to a 2C seismic line from the Llanos Basin (Colombia). This is the first application of the technique in Colombia, initially developed for permafrost zones, with different assumptions and surface complexity; and it resulted in an improved PS converted wave image.